The Effectiveness of Discovery Listening to Improve Listening Competence in Higher Education - Sukma Nur Ardini; Poppy Evita Diah Faradilla; Theresia Cicik Sophia Budiman (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2023)
Abstract. The aim of the research is to investigate the implementation of Discovery Listening. This study focused on the use of the Discovery Listening technique as well as the perception of the students after using Discovery Listening technique. To a great extent, this study wanted to give an account of the study conducted by Ardini, et al. (2020) who applied Wilson’s theory. It was achieved using explanatory sequential mixed-methods research design within 30 students of the 1st semester of Universitas PGRI Semarang. Tests and questionnaire were employed to collect the data which then analyzed using SPSS version 27 and supported by descriptive qualitative data. The result shows the mean score of pre-test was 55.17 and post-test was 72.20. The findings of this study indicated that the implementation of the Discovery Listening technique has improved students’ performance by showing 74% of the students’ score was upgraded and 2 respondents got outstanding achievement from Low to High. Additionally, it can alter the environment of educational activities, transforming a passive class into an active one. The group work also helped the students to overcome their listening problem. Those indicated that it gave positive perceptions from the students, most importantly, the students can learn a new thing. The results of this study can support the previous study from Ardini, et al. (2020) that Discovery Listening is very effective to be applied in higher education as well as increasing students’ critical thinking.Keywords: effectiveness; Discovery Listening technique; higher education; listening competenceAbstrak. Tujuan dari penelitian ini adalah untuk menyelidiki implementasi Discovery Listening. Studi ini berfokus pada penggunaan teknik Discovery Listening serta persepsi siswa setelah menggunakan teknik Discovery Listening. Secara garis besar, penelitian ini ingin memberikan penjelasan tentang penelitian yang dilakukan oleh Ardini, dkk. (2020) yang menerapkan teori Wilson. Penelitian ini dilaksanakan dengan menggunakan desain penelitian metode campuran sekuensial melalui 30 siswa semester 1 Universitas PGRI Semarang. Tes dan kuesioner digunakan untuk mengumpulkan data yang kemudian dianalisis menggunakan SPSS versi 27 dan didukung oleh data kualitatif deskriptif. Hasil penelitian menunjukkan nilai rata-rata pre-test adalah 55,17 dan post-test adalah 72,20. Temuan penelitian ini menunjukkan bahwa penerapan teknik Discovery Listening telah meningkatkan kinerja siswa sebanyak 74% nilai siswa meningkat dan 2 siswa berhasil melompat dari kriteria rendah ke tinggi. Selain itu, dapat mengubah lingkungan kegiatan pendidikan, mengubah kelas pasif menjadi kelas aktif. Kerja kelompok juga membantu siswa untuk mengatasi masalah mendengarkan mereka. Hasil tersebut mengindikasikan adanya persepsi positif dari siswa, yang paling penting, para siswa dapat mempelajari hal baru. Hasil penelitian ini dapat mendukung penelitian sebelumnya dari Ardini, dkk. (2020), bahwa Discovery Listening sangat efektif diterapkan di perguruan tinggi serta meningkatkan berpikir kritis mahasiswa. Oleh karena itu, disarankan kepada peneliti selanjutnya untuk menerapkan Discovery Listening pada jenjang pendidikan yang lebih rendah seperti SMA atau bahkan SD.Kata kunci: efektivitas; keterampilan mendengarkan; pendidikan tinggi; teknik Discovery Listening